Digital-Based Learning Model in Enhancing the Understanding of Aqidah Concepts - Tungkir, Abdul Rasyid; Setiawan, Hasrian Rudi (Integrasi: Jurnal Studi Islam dan Humaniora, 2025)
Digital-based learning models have become an innovation in education, including in Islamic Religious Education (PAI). This study aims to analyze the effectiveness of digital-based learning models in enhancing students' understanding of Aqidah concepts. The research method used is a quantitative approach with an experimental design. The research subjects consisted of secondary school students divided into an experimental group using digital learning models and a control group using conventional methods. Data were collected through pre- and post-intervention Aqidah understanding tests and student perception questionnaires regarding the use of technology in learning. The study results indicate a significant improvement in the understanding of Aqidah concepts in the experimental group compared to the control group. Additionally, students who learned with the digital learning model demonstrated higher levels of motivation and engagement. These findings suggest that implementing digital-based learning models can be an effective alternative to improving Aqidah learning quality.